The LaLiMo Trial: lamotrigine compared with levetiracetam in the initial 26 weeks of monotherapy for focal and generalised epilepsy—an open-label, prospective, randomised controlled multicenter study. Issue 11 (17th May 2012) - Rosenow, Felix; Schade-Brittinger, Carmen; Burchardi, Nicole; Bauer, Sebastian; Klein, Karl Martin; Weber, Yvonne; Lerche, Holger; Evers, Stefan; Kovac, Stjepana; Hallmeyer-Elgner, Susanne; Winkler, Götz; Springub, Joachim; et al.
Abstract : Background: Of the newer antiepileptic drugs, lamotrigine (LTG) and levetiracetam (LEV) are popular first choice drugs for epilepsy. The authors compared these drugs with regard to their efficacy and tolerability in the initial monotherapy for epilepsy. Methods: A randomised, open-label, controlled, parallel group, multicenter trial was conducted to test the superiority of the LEV arm over the LTG arm. The primary endpoint was the rate of seizure-free patients in the first 6 weeks (two-sided Fisher's exact test, α=0.05, intent-to-treat set). Furthermore, efficacy, tolerability and quality of life were evaluated. The authors included 409 patients aged ≥12 years with newly diagnosed focal or generalised epilepsy defined by either two or more unprovoked seizures or one first seizure with high risk for recurrence. Patients were titrated to 2000 mg/day of LEV or 200 mg/day of LTG reached on day 22 or 71, respectively. Two dose adjustments by 500/50 mg were allowed. Results: The proportions of seizure-free patients were 67.5% (LEV) versus 64.0% (LTG) 6 weeks after randomisation (p=0.47), and 45.2% (LEV) versus 47.8% (LTG) during the whole treatment period of 26 weeks. The HR (LEV vs LTG) for seizure-free time was 0.86 (95% CI, 0.61 to 1.22). Adverse events occurred in 74.5% (LEV) versus 70.6% (LTG) of the patients (p=0.38). Adverse events associated with study discontinuation occurred in 17/204 (LEV) versus 8/201 (LTG) patients (p=0.07). Conclusions: There were no significant differences with regard to efficacy and tolerability of LEV and LTG in newly diagnosed focal and generalised epilepsy despite more rapid titration in the LEV arm. Clinical trial registration number: ClinicalTrials.gov identifier NCT00242606 .